Digital services and social stability: the impact from a maqasidic approach - Bendebka, Ramzi; Fettane, Amar; Shogar, Ibrahim (Knowledge E Publisher, 2022)
During the Covid-19 epidemic, there was an urgent need for many countries to move as quickly as possible towards digital services such as e-government, e-learning and ecommerce. The positive aspects of this transformation cannot be overlooked, however, other negative effects may result from the long and medium-term of such an approach. For instance, not all governments have the ability to provide Internet access to serve the interests of their citizens. Therefore, this research will question the effects of the increasing trend towards digital services and how can they affect societal stability? Furthermore, how can these effects be dealt with from a Maqasidic perspective? To answer these questions, the researchers used the holistic approach to collect information on the subject matter and related concepts, terms and opinions related to digital services and social stability. Also, the analytical approach showed the effects of digital services on social stability with a specific focus on Maqasid Shariah. Among the most important results of the research are that: quality of information accessibility, equality, social trust, social cohesion and community engagement are the main aspects that can be affected by digital services. Therefore, moving towards digital services must be directed by Maqasid al-Shariah as a frame to maintain social stability and peace.